PERAN EMOTION REGULATION DALAM MEMPENGARUHI TINDAKAN CYBER AGGRESSION PADA REMAJA - Jessica Aprilia Fernanda; Dyan Evita Santi; Allifia Ananta (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
This study aims to determine the relationship between social comparison and self- esteem with social anxiety in adolescent Instagram social media users. This study is a quantitative research type using quantitative correlational methods. The sampling technique in this study used the purposive sampling method with a sample size of 243 adolescent Instagram users at Sunan Giri High School. The results of multiple regression analysis showed that the relationship between social comparison and self-esteem simultaneously with social anxiety (F count value = F table = 58.804 with a significance of 0.000<0.05) which means there is a significant relationship between social comparison and self-esteem with social anxiety in adolescent Instagram users. The results of the partial test showed that there was a significant positive relationship between social comparison and social anxiety. The results of the partial test showed that there was a significant negative relationship between self-esteem and social anxiety, meaning that the hypothesis in this study was accepted.